Case report: Beneficial long-term effect of the atrial-flow-regulator device in a pediatric patient with idiopathic pulmonary arterial hypertension and recurring syncope - Joseph Pattathu; Sebastian Michel; Anja Ingrid Tengler; Guido Mandilaras; Andre Jakob; Robert Dalla Pozza; Nikolaus A. Haas (Frontiers in Cardiovascular Medicine, 2023)
We report the long-term effect after successfully implanting an 8 mm Atrial-flow-regulator (AFR) device in a 7-year-old girl with idiopathic pulmonary hypertension with persistent syncope under triple therapy with significant improvement after implantation and absence of any further syncope. Early Implantation of the AFR device (Occlutech, Germany) can be efficient and safe interventional therapy option for pulmonary arterial hypertension with a history of syncope.